Oxidation behavior of NiCrAlYSi coatings with Re-based diffusion barriers on two superalloys. (15th April 2022) - Fu, L.B.; Zhang, W.L.; Li, S.M.; Li, Y.T.; Li, W.; Sun, J.; Wang, T.G.; Jiang, S.M.; Gong, J.; Sun, C.
Abstract: The NiCrAlYSi coatings with or without Re-based diffusion barriers (DB) were prepared on K438 and K465 superalloys by electroplating Re-Ni layer, arc ion plating (AIP) NiCrAlYSi coating and following vacuum annealing. Isothermal oxidation behaviors of all coatings were investigated at 1100 ℃ in static air. The results showed that better oxidation resistance was achieved for NiCrAlYSi coatings with Re-based DB and for NiCrAlYSi coatings on K438 than that on K465. Re diffused into NiCrAlYSi coatings during isothermal oxidation and increased spallation resistance of oxide scale. The role of Re-based DB and the effects of substrate compositions were discussed. Highlights: The dual roles of Re-based DB were found for NiCrAlYSi coating with it. NiCrAlYSi coatings with DB transformed to Re modified coatings during oxidation. Re diffusing in NiCrAlYSi coatings increased spallation resistance of oxide scale. Cr and W in substrate had an important impact on oxidation resistance of coating. The outward diffusion of W from substrate to Re-based DB made it more stable.